Maniobras de llenado y vaciado en grandes conducciones. Aplicación a una tubería de fundición DN400 en Massamagrell (Valencia, España) (2020)
Air pockets inside hydraulic installations during filling and emptying processes can generate pressure surges and negative pressure, respectively. Serious damages can be occurred in pipelines. In order to analyse hydraulic variables in filling and emptying operations, the selection of a mathematical model is chosen, which is suitable of simulating accurately the behaviour of both fluids (water and air) in pressurized water systems. The mathematical model proposed by the authors has been validated in small laboratory facilities. The aim of this work is to validate the mathematical model in current pipeline installations with large both nominal diameter and length. The pipeline is a nominal diameter DN400, and is located in Massamagrell, Valencia, Spain. The filling and emptying manoeuvres in the selected pipeline are performed by the Empresa Mixta Metropolitana S.A. (EMIMET). A good agreement is obtained when a comparison of absolute pressure and water flow is carried out between the mathematical model and the measurements.